2014
DOI: 10.1039/c4dt00823e
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeting phosphorescent iridium(iii) complexes for living cell imaging

Abstract: Two phosphorescent iridium(III) complexes conjugated to a lipophilic triphenylphosphonium cation moiety, IrMitoOlivine and IrMitoNIR, were synthesized. The complexes show high mitochondria-specificity and relatively lower cytotoxicity. Time-lapse confocal imaging indicates that both complexes exhibit an excellent anti-photobleaching capability under continuous laser irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…In previous research, we found that some Ir III complexes possess high specificity for mitochondria and superior photostability, and can be used for mitochondrial imaging and tracking 9. 12c, 16 More importantly, Ir III complexes have been developed as two‐photon mitochondrial probes 16d. e In the present work, to obtain specific novel complexes for mitochondrial two‐photon phosphorescent probes, a series of 2‐phenylimidazo‐[4,5‐][1,10]phenanthroline derivatives that exhibited excellent light‐emitting efficiency were synthesized and conjugated to iridium(III).…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, we found that some Ir III complexes possess high specificity for mitochondria and superior photostability, and can be used for mitochondrial imaging and tracking 9. 12c, 16 More importantly, Ir III complexes have been developed as two‐photon mitochondrial probes 16d. e In the present work, to obtain specific novel complexes for mitochondrial two‐photon phosphorescent probes, a series of 2‐phenylimidazo‐[4,5‐][1,10]phenanthroline derivatives that exhibited excellent light‐emitting efficiency were synthesized and conjugated to iridium(III).…”
Section: Introductionmentioning
confidence: 99%
“…All of these dyes can efficiently image mitochondria in living cell. [15][16][17][18][19][20][21][22][23][24][25][26][27] In addition, some cyclometalated iridium(III) complexes exhibit appealing optical properties, such as aggregation-induced emission, 16,21 two-photon phosphorescence, 22,23 and near infrared emission 18,24 . 10 These organic agents are unable to perform long-time observations due to their poor photostability.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic routes and the structure characterization of Ir-COOH can refer to the former literature. [41] As shown in Figure 2, beside the well-known absorption in UV regions (< 350 nm), Ir-COOH in this work also has moderate absorption in visible light regions from 450 nm to 600 nm and the molar extinction coefficient (e) is 7750 M À1 cm À1 at 532 nm. Under the excitation of 532 nm (Xe lamp) Ir-COOH in this work has nearinfrared emission with maxima at 713 nm and 783 nm.…”
Section: Main Textmentioning
confidence: 50%
“…The chemical structure of Ir–COOH has been shown in Figure . The synthetic routes and the structure characterization of Ir–COOH can refer to the former literature . As shown in Figure , beside the well‐known absorption in UV regions (< 350 nm), Ir–COOH in this work also has moderate absorption in visible light regions from 450 nm to 600 nm and the molar extinction coefficient (ϵ) is 7750 M −1 cm −1 at 532 nm.…”
Section: Main Textmentioning
confidence: 77%